On Sets with Extremely Big Slices - Ivakhno, Yevgen (Журнал математичної фізики, аналізу, геометрії, 2006)
A new characterization of the Radon-Nikodym property in terms of sizesof slices and equivalent norms is presented. A property opposite to theRadon-Nikodym property is studied in the context of 1-unconditional sums of Banach spaces. Mathematics Subject Classification: 46B20, 46B22, 46G10, 46B03.